Decriminalization of Omnibus Law To Enhance Investment In Indonesia - Gede Aditya Pratama, Gede Aditya Pratama (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
This study explains decriminalization through Omnibus Law as a means to attract investment to Indonesia. Omnibus Law enacted in November 2020 has revoked 17 penal articles and revised another 50 penal articles to “material delict”. This was done to boost the confidence of investors and business actors, so they are more comfortable putting their investments and running their businesses in Indonesia. The policy of decriminalization is something that is equitable to do. This is done because of several factors that are taken into considerations, such as political and economic reasons. With the national priority of Indonesia now is towards the recovery of its economy through investment amid the COVID-19 pandemic, it is not strange that this decriminalization policy through Omnibus Law was taken. However, the effectiveness of it to reach its goal still needs time to prove.